2021
DOI: 10.5334/johd.29
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Views on a Global Pandemic: Social and Cultural Effects of the Covid-19 Pandemic as Documented in Two Dutch Community Archives

Abstract: The COVID-19 pandemic, in addition to the obvious implications for public health and the economy at a global scale, has also had significant social and cultural effects: the partial or complete lockdown of public life breaks social and cultural networks and habits, and necessitates the invention of new forms of communication, contact, and inspiration. Over the course of the pandemic, various initiatives have emerged that have tried to capture this unique moment in history by collecting documentation on the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…They found that photovoice contributed to strengthening their personal and collective resilience [ 36 ]. Similarly, Noordegraaf et al pointed out the emergence of a perceived inside/outside duality among the people in the cities in lockdown through qualitative analyses of two such citizen-generated collections of experiences with the CoV19 pandemic [ 44 ]. This culminated in ‘ Corona in the City ’, assembled by the Amsterdam Museum for an online exhibition.…”
Section: Social Participation Of Citizensmentioning
confidence: 99%
“…They found that photovoice contributed to strengthening their personal and collective resilience [ 36 ]. Similarly, Noordegraaf et al pointed out the emergence of a perceived inside/outside duality among the people in the cities in lockdown through qualitative analyses of two such citizen-generated collections of experiences with the CoV19 pandemic [ 44 ]. This culminated in ‘ Corona in the City ’, assembled by the Amsterdam Museum for an online exhibition.…”
Section: Social Participation Of Citizensmentioning
confidence: 99%